Напівпровідникова галузь: досвід країн ЄС та перспективи України - Утюж, М.В. (Економіка промисловості, 2025)
Напівпровідникова галузь відіграє провідну роль у зміцненні економічної та технологічної безпеки, є важливим чинником інноваційного розвитку. У відповідь на глобальні виклики Європейський Союз упроваджує комплекс заходів: законодавчу ініціативу EU Chips Act, формування виробничих кластерів, підтримку інновацій і співпрацю з Японією, Південною Кореєю та Тайванем. Значну увагу приділено узгодженню промислової та енергетичної політики, розвитку нових матеріалів (GaAs, SiGe, InP), формуванню стратегічної автономії з метою зменшення залежності від іноземних постачальників. Виявлено можливість адаптації цього досвіду в Україні для модернізації напівпровідникового сектору як базису інноваційно-технологічного розвитку країни. The semiconductor industry is a cornerstone of the European Union’s economic resilience and technological sovereignty, forming a critical pillar of modern industrial policy. In response to growing geo-economic tensions, supply chain vulnerabilities, and technological dependence on third countries, the EU has intensified its efforts to regain strategic autonomy. These efforts are embodied in the adoption of the EU Chips Act, which provides a comprehensive regulatory and financial framework to expand semiconductor production capacities within the EU. Complementary initiatives include the creation of regional innovation clusters (Silicon Saxony, Grenoble Valley, Eindhoven), the development of next-generation materials such as gallium arsenide (GaAs), silicon-germanium (SiGe), and indium phosphide (InP), and the reduction of critical material dependencies through diversification of imports and strategic partnerships with like-minded nations, including Japan, South Korea, and Taiwan. In this context, the article provides a systematic analysis of the EU’s semiconductor policy and identifies tools that can be adapted to Ukraine’s post-war recovery and long-term economic development. Given Ukraine’s legacy in microelectronics, scientific potential, and role as a key supplier of rare gases such as neon and palladium, the country possesses the foundations to rebuild a resilient semiconductor ecosystem. The study highlights Ukraine’s opportunity to develop specialized production capacities in SiGe-based radiofrequency chips and GaN-based power electronics, which are in high demand for defense, space, and next-generation communication systems. Special attention is paid to institutional constraints, such as underfunded R&D, workforce shortages, and weak IP protection, which hinder Ukraine’s technological revival. The paper proposes practical policy recommendations, including the implementation of forward-looking industrial policy, integration into EU value chains, and alignment with European research initiatives (Horizon Europe, Digital Europe). It also emphasizes the importance of building domestic production hubs, developing export-oriented competencies, and leveraging public-private partnerships to attract investments in the semiconductor sector. Overall, the paper underscores the strategic potential of adapting the EU’s industrial model to Ukraine’s context, advocating for the formation of a high-tech national semiconductor strategy. Such an approach would not only strengthen Ukraine’s defense capabilities and economic sovereignty but also position the country as a valuable partner in the broader European technology landscape.